The role of cortical beta oscillations in time estimation. Issue 9 (11th May 2016) - Kulashekhar, Shrikanth; Pekkola, Johanna; Palva, Jaakko Matias; Palva, Satu
Abstract: Estimation of time is central to perception, action, and cognition. Human functional magnetic resonance imaging (fMRI) and positron emission topography (PET) have revealed a positive correlation between the estimation of multi‐second temporal durations and neuronal activity in a circuit of sensory and motor areas, prefrontal and temporal cortices, basal ganglia, and cerebellum. The systems‐level mechanisms coordinating the collective neuronal activity in these areas have remained poorly understood. Synchronized oscillations regulate communication in neuronal networks and could hence serve such coordination, but their role in the estimation and maintenance of multi‐second time intervals has remained largely unknown. We used source‐reconstructed magnetoencephalography (MEG) to address the functional significance of local neuronal synchronization, as indexed by the amplitudes of cortical oscillations, in time‐estimation. MEG was acquired during a working memory (WM) task where the subjects first estimated and then memorized the durations, or in the contrast condition, the colors of dynamic visual stimuli. Time estimation was associated with stronger beta (β, 14 − 30 Hz) band oscillations than color estimation in sensory regions and attentional cortical structures that earlier have been associated with time processing. In addition, the encoding of duration information was associated with strengthened gamma‐ (γ, 30 − 120 Hz), and the retrieval and maintenance with alpha‐ (α, 8 − 14 Hz) band oscillations. These data suggest that β oscillations may provide a mechanism for estimating short temporal durations, while γ and α oscillations support their encoding, retrieval, and maintenance in memory. Hum Brain Mapp 37:3262–3281, 2016 . ©2016 Wiley Periodicals, Inc.